Adsorption and Electrochemical Oxidation of Small Sulfur−Containing Anions on Pt Electrodes in Organic Media. Issue 16 (30th May 2018) - Chen, Chang‐Hui; Brennan, Colin; Lai, Stanley C. S.; Fermin, David J.; Unwin, Patrick R.; Rodriguez, Paramaconi
Abstract: Acetic acid is an important organic solvent for the chemical industry, such as in catalytic hydrogenation and for electrosynthesis reactions generally. In this work, the adsorption and electrochemical oxidation of several sulfur‐containing anions (S 2−, S2 O4 2−, S2 O5 2− and SO3 2− ) over Pt electrodes in a mixture of sulfuric acid/acetic acid was investigated by using cyclic voltammetry. Electrochemical oxidation provides a means of regenerating Pt catalysts and the sulfur‐containing anions studied are examples of species that might be produced under synthetic conditions or could be present as impurities in industrial feedstock. To determine the oxidation reaction mechanism and its surface‐structure sensitivity, Pt polycrystalline and single‐crystal electrodes are implemented in this study. It is found that the oxidation of the sulfur‐containing species on Pt polycrystalline electrode takes place at higher potentials in comparison to the same reactions in aqueous media. This is attributed to the low coverage of surface oxide, owing to the low concentration of water and the adsorption of acetate at the surface. Experiments on the Pt basal planes and stepped surfaces reveal a strong surface‐structure dependence for the oxidation of all the sulfur‐containing species. These results provide valuable information that will aid the engineering of nanocatalysts with specific crystalline structure less prone to contamination during catalytic process in mixtures of sulfuric/acetic acid. Abstract : Electrochemical recovery : Electrochemical oxidation provides a means to eliminate surface sulfur‐poisoning species such as (S 2−, S2 O4 2−, S2 O5 2− and SO3 2− ) from the surface of Pt catalysts. Pt single‐crystal electrodes reveal surface‐structure sensitivity of the electro‐oxidation of the adsorbed sulfur species.